Analisis Kemampuan Number Sense Matematis Siswa ditinjau dari Motivasi Belajar Siswa Pada Materi Bilangan Bulat di Kelas VII Mts Al-Fattah Singkawang - Winda Septiani; Rika Wahyuni; Nurul Husna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to describe the level and influence of motivation that affects students' mathematical number sense ability on integer material viewed from the learning motivation of class VII students of MTS Al-Fattah Singkawang. This research method is descriptive with qualitative research type. The subjects in this study were 30 class VII C students. The objects in this study are mathematical number sense ability and students' learning motivation on integer material. Data collection using student motivation questionnaires and instruments in the form of descriptive tests that are adjusted to the number sense ability indicators and have been tested using content validation, construct validation, reliability, discriminatory power, and level of difficulty. The data analysis techniques used are questionnaire data analysis and test data analysis (scoring, data description, and interviews). The research results obtained are; 1) The level of mathematical number sense ability viewed from high learning motivation is at the medium level of number sense ability, 2) The level of mathematical number sense ability viewed from medium learning motivation is at the medium level of number sense ability, 3) The level of mathematical number sense ability viewed from low learning motivation is at the medium level of number sense ability 4) Factors of student learning motivation that affect number sense ability include; 1) the surrounding environment 2) students are less enthusiastic in learning 3) students' memory decreases 4) students' lack of understanding.